BAS/BSCR46 X-box binding protein 1 splicing triggers an autophagic survival pathway in endothelial cells. Issue 17 (26th August 2010) - Margariti, Andriana; Li, Hongling; Martin, Daniel; Zampetaki, Anna; Hu, Yanhua; Xu, Qingbo; Zeng, Lingfang
Abstract : An initial step in the development of atherosclerosis is endothelial cell dysfunction. Our previous study has shown that sustained activation of X-box binding protein 1 (XBP1) splicing, a key signal transducer in endoplasmic reticulum stress response, leads to endothelial apoptosis and atherosclerosis development (Zeng et al, PNAS 2009). Autophagy is characterised as a survival response as well as a pathway culminating in cell death. In this study, we aimed to investigate whether XBP1 splicing could also activate autophagy in endothelial cells, and its role in the cell survival and apoptosis. XBP1 splicing was introduced to human umbilical vein endothelial cells by adenoviral gene transfer, and autophagic vesicle formation was observed 48 and 72 h postinfection. Autophagy gene expression such as Beclin 1, LC3-β, NIX, ATGF-tv1, BNIP2, BNIP3, ATG5 and ATG12 was induced by XBP1 splicing as detected at RNA and protein levels. Endothelial cells transfected with the LC3β-GFP construct showed a high GFP expression of autophagic vesicle formation only in the presence of spliced XBP1 compared with the non-infected cells. Moreover, our results showed that endostatin, a well-characterised endogenous inhibitor of angiogenesis that induces apoptosis, activated autophagy genes 4 h after treatment, through XBP1 splicing in an IRE1-α-dependent manner. Knockdown of XBP1 or IRE1α by ShRNA in endothelial cells ablated endostatin-induced autophagy responsive genes expression and enhanced the apoptotic effect of endostatin. These results suggest that activation of XBP1 splicing can trigger an autophagic survival signal pathway, providing novel insights into the mechanisms involved in endothelial survival.